Hubungan Kepribadian Otoritarian Dengan Pemidanaan Hakim - Yusti Probowati Rahayu (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2007)
Disparity of Sentences is defined as disparate sentencing toward the relative same criminal cases. The sentencing disparity lead to the rise unsatisfactory feeling. The purpose of this research was to know the effect of the authoritarian personality of The judges to the sentencing disparity.          90 subject of the research were 77 judges and 13 candidate of judges at the court of the first instance in DIY and Centre Java. They should make decision on the same criminal case, and filled the authoritarian scale. The data was analyzed with one way anova.          The result of this research showed that there was large sentencing disparity ( 0 to 126 months) although has been used a similar case. The Authoritarian personality of the judges had effect to the sentencing disparity. The judges with high authoritarian personality give severe sentence than the judges with middle and low authoritarian personality. This research suggested to The Law Department to reduce the authoritarian personality of judges. Keywords :   The sentencing of the judges, the authoritarian personality of judges,  the disparity of sentencing.